The changes of adaptability and productivity of the winter bread wheat varieties in arid conditions according to the stages of variety changing - Е. V. Ionova; V. А. Likhovidova; V. L. Gaze (Зерновое хозяйство России)
The current paper has presented the study results on the change of adaptability to water and temperature stresses and the value of productivity according to the stages of variety changing. There have been selected 13 winter bread wheat varieties developed in the FSBSI Agricultural Research Center “Donskoy”. It was found that the varieties of the first stages of the variety changing (I–IV stage, 1950–1989) practically did not differ in the degree of drought tolerance and the value of productivity of winter bread wheat. In this regard, there was carried out an analysis of changes in the adaptability of winter wheat varieties starting from the V stage of the variety changing. The degree of drought tolerance increased from the weakly-medium drought-resistant varieties (37.4–51%) belonging to the V stage of the variety changing to highly drought-resistant samples (80.4–93.3%) belonging to the VII stage of the variety changing. There was a significant productivity increase of the winter bread wheat varieties zoned from 2010 to 2019 (the VII stage of the variety changing). The largest number of stomata per unit of leaf area in the V stage of the variety changing was identified in the variety ‘Don 95’ (12.2 pcs/mm2). In the VI stage of the variety changing, the largest value of this indicator was identified in the variety ‘Don 105’ (18.8 pcs/mm2), and in the variety ‘Krasa Dona’ (26.9 pcs/mm2) in the VII stage of the variety changing. The dry weight of roots of the varieties of the V stage of the variety changing varied from 1.18 (the variety ‘Donshchina’) to 1.41 g (the variety ‘Don 95’), while in varieties of the VI stage this indicator varied from 1.97 (the variety ‘Donskoy Mayak’) to 2.29 g (the variety ‘Don 105’), and the largest dry weight of roots was identified at the VII stage of the variety changing and ranged from 2.34 (the variety ‘Don 107’) to 2.79 (the variety ‘Asket’). The same regularity was established for the change in the amount of roots according to the stages of variety changing.